The Influence of Corporate Governance Practices and Ownership Structure on Credit Ratings: Evidence from Indonesia - Utama, Cynthia Afriani; Utama, Sidharta; M. Amin, Ahmad (Asian Journal of Business and Accounting, 2016)
Manuscript type: Research paper Research aims: This study aims to investigate the influence of corporate governance practices and ownership structure on the credit ratings of listed firms in Indonesia. Design / Methodology / Approach: This study empirically employs the ordered logit model and a corporate governance measure that is based on OECD corporate governance principles. Research findings: This study finds that corporate governance practices reduce agency problems between creditors and shareholders. This is reflected by their positive impact on firm credit ratings. The results of the tests further show that credit ratings are affected positively by share ownership held by blockholders. Thus, higher concentrated ownership provides oversight functions which could lead to higher debt ratings. However, when blockholders are from families, the possibility of expropriation increases and this, in turn, reduces debt ratings. Theoretical contributions / Originality: This study examines the effect of a comprehensive measure of corporate governance practices and families as blockholders on firms’ credit ratings. Practitioner / Policy implications: Firms need to improve their corporate governance practices in order to facilitate the issuance of long term debt at lower yield. Research limitations / Implications: This study has limited observations that may affect the power of statistical test. Future studies should increase sample size, extend the period of the study and employ more recent data. Keywords: Corporate Credit Ratings, Corporate Governance Practice, Firm Default Risk, Ownership Structure JEL classification: G30, G34